The Role of Stock Markets in Current Account Dynamics : Evidence from the United States - Mercereau, Benoit (IMF Working Papers; Working Paper ;, 2003)
This paper tests a model of the role of stock markets in current account dynamics, developed in a companion paper. With U.S. data, the model performs better than the same model without stock markets. An insight given by the model is that the current account might help predict future stock market performance. This property receives some preliminary empirical confirmation. The results also suggest that stock markets matter to the current account dynamics.